Synthesis, antimicrobial, antioxidant studies of thermally stable nanocomposite films doped with CoO-NPs for active food packaging applications - Maqam Ali; Muhammad Kaleem Khosa; Awal Noor; Sadaf Qayyum (PLoS ONE, 2025)
This research work presents a fabrication and study to explore different features of Gelatin/ Polyethylene glycol/ Chitosan ternary composite films doped with cobalt oxide nanoparticles. Such films were prepared by solution casting technique coupled with sonication with varying concentrations of CoO-NPs (0.5%–2.5%). Multiple techniques like, FT-IR, XRD, SEM, TGA and DMA were used to characterize and test their stability. FT-IR and XRD confirmed the cross-linking among the biopolymers and metal oxide nanoparticles. Smooth surface morphology was observed by SEM while TGA and DMA was used to determine the thermal stability and flexibility of nanocomposites. The flexibility (EB) and tensile strength of the GPC blend was found to be considerably increased by the addition of CoO-NPs up to 2.5%. It has been also observed that as the concentration CoO-NPs in gelatin/polyethylene glycol/Chitosan, increased (up to 2.5%), the nature of GPC composites films changed from hydrophilic to hydrophobic After the characterization, the synthetic nanocomposites films were subjected to antibacterial and antioxidant analysis. The nanocomposites films showed significant activity against S. aureus and E. coli , and were further applied to antibiofilms formation activity. Results showed that, increased thermal stability and flexibility, reduced moisture absorbance, water permeability, good antibacterial, antioxidant and antibiofilm activities against foodborne pathogens make them good choice for active food packaging applications.